A categorical dea framework for evaluating medical tourism efficiency of "top destinations" - Karadayı, Melis Almula; Işık, Mine (Springer, 2018)
Over the past decade, medical tourism has been one of the fastest growing sectors in developing countries. In this context, the attempt to monitor the performance of top medical tourism destinations has become a major concern. In spite of the fact that medical tourism has a significantly direct impact on not only GDP but also foreign exchange generation, there is an absence of empirical studies on the key drivers. This study proposes a categorical data envelopment analysis (DEA) framework for evaluating medical tourism performance of top destinations. Finally, research hypotheses are created to analyze the relationship between the countries’ medical tourism performance and their political, regulatory environment, technology and knowledge outputs.
WOS: 000442508400020
Keywords: Categorical Data; Data Envelopment Analysis; Efficiency; Medical Tourism; Performance Evaluation